Validating a self-report measure of HIV viral suppression: an analysis of linked questionnaire and clinical data from the Canadian HIV Women’s Sexual and Reproductive Health Cohort Study - Carter, Allison (BMC Res Notes, 2017)
BACKGROUND: We assessed the validity of a self-report measure of undetectable viral load (VL) among women with HIV in British Columbia (BC), Canada. Questionnaire data from the Canadian HIV Women’s Sexual and Reproductive Health Cohort Study was linked with population-based clinical data from the BC Centre for Excellence in HIV/AIDS. Self-reported undetectable VL was assessed by the question: “What was your most recent VL, undetectable (i.e. <50 copies/mL) or detectable (i.e. ≥50 copies/mL)?” Laboratory measurements of VL <50 copies/mL (closest to/before study visit) were the criterion for validity analyses. We measured positive and negative predictive values (PPV, NPV) and likelihood ratios (LR+, LR−). RESULTS: Of 356 participants, 99% were linked to clinical data. Those unlinked (n = 1), missing self-report VL (n = 18), or missing self-report and laboratory VL (n = 1) were excluded. Among the remaining 336: median age was 44 (IQR 37–51); 96% identified as cis-gender; 84% identified as heterosexual; and 45% identified as Indigenous, 40% White, 8% African, Caribbean, or Black, and 8% other/multiple ethnicities. Overall, 85% self-reported having an undetectable VL while 82% had clinical data indicating viral suppression. The PPV was 93.7 (95% CI 90.2–96.2) indicating that 94% of women who self-reported being undetectable truly were. The NPV was 80.4 (95% CI 66.9–90.2). LR+ was 3.2 (2.1–4.6) and LR− was 0.05 (0.03–0.10). CONCLUSIONS: Our self-report measure assessing undetectable VL strongly predicted true viral suppression among Canadian women with HIV. This measure can be used in research settings without laboratory data in regions with high rates of VL testing and suppression.